Relationship between the Structure and Transport Properties in the Ce1−xLaxO2−x/2 System - Zamudio-García, Javier; Porras-Vázquez, José Manuel; Canales-Vázquez, J.; Cabeza-Díaz, Aurelio; Losilla, Enrique R.; Marrero-López, David (American Chemical Society, 2019)
La-doped CeO2 materials have been widely investigated for potential applications in different high-temperature electrochemical devices, such as fuel cells and ceramic membranes for hydrogen production. However, the crystal structure is still controversial, and different models based on fluorite, pyrochlore, and/or type-C structures have been considered, depending on the lanthanum content and synthesis method used. In this work, an exhaustive structural analysis of the Ce1−xLaxO2−x/2 system (0.2 < x ≤ 0.7) is performed with different techniques. The average crystal structure, studied by conventional X-ray diffraction, could be considered to be a disordered fluorite; however, the local structure, examined by electron diffraction and Raman spectroscopy, reveals a biphasic mixture of fluorite and C-type phases. The thermal and electrical properties demonstrate that the materials with x ≥ 0.4 are oxide ion proton conductors in an oxidizing atmosphere and mixed ionic electronic conductors in a reducing atmosphere. The water uptake and proton conductivity increase gradually with the increase in La content, suggesting that the formation of the C-type phase is responsible for the proton conduction in these materials.
Keywords: Pilas de combustible; Catalizadores; Proton-conductivity; CeO2